On a small collection of harpacticoids from Easter Island: the family Laophontidae T. Scott (Crustacea: Copepoda: Harpacticoida) - Gómez, Samuel; Boyko, Christopher B. (Zootaxa, 2006)
The harpacticoid family Laophontidae T. Scott is reported from Easter Island for the first time. A provisional redescription of both sexes of the type species of Laophonte Philippi, Laophonte cornuta Philippi, is provided based on newly collected material from Motu Iti, Easter Island. A second species of the cornuta-group, Laophonte similicornuta sp. nov. is described based on a single female. Two other new species belonging to the subfamily Laophontinae T. Scott are described, Phycolaophonte tongariki sp. nov. (based on a single female) and Loureirophonte minutum sp. nov. (based on a male only). An updated generic diagnosis for Phycolaophonte is given, as well as an amendment to Fiers' (1993) key to the species of Loureirophonte Jakobi. A fourth species-group is recognised within the genus, the minutum-group, which is defined by the combination of: P4ENP being represented by a single seta, presence of 3 and 2 outer spines on the P2–P3EXP3 and P4EXP3, respectively, and presence of a normal outer spine on the male P3EXP2. Within the Esolinae Huys and Lee, Corbulaseta pacifica sp. nov. is described based on a single female. Reexamination of Vervoort's (1962) concept of Corbulaseta (=Esola) bulligera (Farran) from New Caledonia revealed a distinct species of the genus Corbulaseta, described herein as C. tokiokai sp. nov. Intrageneric relationships of the new species described and biogeographic affinities are discussed.